Poverty, food prices, and dietary choices in Malawi - Pauw, Karl; Verduzco-Gallo, Íñigo; Ecker, Olivier (International Food Policy Research Institute, 2018)
This chapter reports on the links between household food consumption choices, food prices, and household income, using data from Malawi’s Second (2004–2005) and Third (2010–2011) Integrated Household Surveys. Results indicate that while income poverty appears to have decreased on average, substantial disparities remain and are indeed increasing, with the richest quintile becoming disproportionately better off, and the poorest of the poor becoming even worse off, a trend that may well shape nutritional outcomes in the future. Further, all but the richest households appear to be spending more money on food than in the past, although much of this trend is likely explained by a relative decline in the cost of nonfood goods. Trends in food consumption appear mixed. They include some predictable responses. For example, with respect to maize nationwide, prices decreased and consumption increased, while for leafy greens, prices increased and consumption decreased nationwide. More unpredictable responses were also observed. These include an increase in consumption of red meat, fruit, rice, and fish nationwide, despite rising prices for all four commodities. Based on these results, indicators for household-level access to micronutrients were constructed to estimate household access to vitamin A and iron, as well as total calories. Results indicate substantial shortfalls across income quintiles for iron in rural areas, and vitamin A shortfalls nationwide. And while access to calories improved overall, significant differences exist in the levels and rate of decline in rural and urban areas, with the improvement in urban households being far greater.